An orthopedic implant with antibacterial and osteogenesis properties and a preparation method thereof
By forming a multi-layer structural coating on the titanium stent and loading drugs, the problem of infection and integration difficulties after implantation of orthopedic endophytes is solved, and the effect of antibacterial, bone and biological fixation is achieved.
Patent Information
- Application Number
- CN202411934061.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Existing orthopedic endoplants are prone to infection and loose implants after implantation, and the integration of the endoplant with host bones is poor due to the decrease in bone growth ability of elderly patients and postmenopausal women.
By forming a sodium titanate coating, a hydroxyapatite coating and a porous hydrogel coating on the titanium scaffold, and finally loading drugs into the porous hydrogel coating, an orthopedic endophyte with antibacterial and bone-promoting properties is formed.
This method can not only effectively prevent implant-related infections, improve osteointegration and osteogenic activity, but also extend the survival time of endoplant through the drug's sustained release effect and reduce the risk of postoperative revision.
Smart Images

Figure CN119345456B_ABST
Abstract
Description
Technical Field
[0001] The present invention is an orthopedic implant with antibacterial and osteogenic properties and a preparation method thereof, and specifically relates to an orthopedic implant with antibacterial properties and the ability to promote osteogenic differentiation of bone marrow mesenchymal stem cells and biological fixation, belonging to the technical field of medical materials. Background Art
[0002] For orthopedic implants such as biological joint prostheses and metal pads for repairing bone defects, the two most catastrophic complications currently faced are implant-related infection and implant loosening. As one of the most serious complications after the implantation of orthopedic implants such as joint prostheses, implant-related infection will not only greatly increase the patient's pain, delay recovery time, and increase medical expenses, but may also increase the patient's postoperative disability and mortality rate. Orthopedic implant-related infection is one of the major challenges faced by orthopedic surgeons and infectious disease physicians. Therefore, it is of great significance to reduce the occurrence of orthopedic implant-related infection. Orthopedic implant postoperative infection is mostly caused by intraoperative contamination. At present, intravenous antibiotics are used clinically to prevent infection. This method has the disadvantages of low local blood drug concentration, large systemic toxicity and side effects, large dosage, and frequent administration. The main cause of orthopedic implant infection is the adhesion and colonization of bacteria on its surface, which then forms a biofilm. Due to the formation of biofilm and the low blood supply around implants such as prostheses, the efficacy of systemic intravenous antibiotics is very limited, which will eventually cause persistent inflammation and necrosis of surrounding tissues, leading to implant failure. Modifying the surface of orthopedic implants and loading them with antibiotics may be an effective measure to prevent and reduce implant-related infections.
[0003] For orthopedic implants such as biological joint prostheses and metal pads for repairing bone defects, excellent bone ingrowth ability is particularly important for promoting bone integration between the implant and the host bone, thereby achieving good bone ingrowth. However, most patients who undergo joint replacement are elderly patients and postmenopausal women. These groups have poor bone ingrowth effects due to their own decreased bone ingrowth ability, decreased integration ability between the implant and the host bone. Therefore, constructing implants with excellent bone ingrowth ability is of great significance for promoting bone integration.
[0004] In the prior art, Chinese patent CN112663057A discloses a method for preparing a hydroxyapatite / drug-loaded hydrogel composite coating on a micro-arc oxidized titanium surface. The method first forms a micro-arc oxidized coating on the surface of a titanium sample by a micro-arc oxidation method, and forms a hydroxyapatite bioactive coating on the micro-arc oxidized titanium surface. Then, a PDMS template prepared from a mixture of a dimethylsiloxane (PDMS) prepolymer and a curing agent is used, and the PDMS template is cured by ultraviolet light to form a porous structure and a nanorod-shaped composite coating of a drug-loaded hydrogel solution of chitosan and sodium alginate on the sample surface, thereby improving the bonding strength and bioactivity of the implant to the bone. At the same time, the drug-loaded composite hydrogel is loaded on the surface of the micro-arc oxidized titanium through the PDMS template, which also gives the implant coating more biological functions. However, the patented method still has complex preparation process and certain safety hazards. For example, the micro-arc oxidation technology and homemade PDMS template are needed in the preparation process to prepare photocurable gel on titanium sheet. Sodium alginate and chitosan need to be chemically modified with double bonds. The safety of the modified products is unknown and they have not been certified by FDA. It is unclear whether they can be clinically transformed. At the same time, the use of photoinitiators may also cause biosafety risks. Moreover, when the drug is added at one time during photocuring, ultraviolet light may also denature the drug. Based on these factors, the clinical transformation and industrialization prospects of this patented method are not ideal. Summary of the invention
[0005] The purpose of the present invention is to provide an orthopedic implant with antibacterial and osteosynthesis-promoting properties and a preparation method thereof, wherein a multilayer structure of a sodium titanate coating, a hydroxyapatite coating and a porous hydrogel coating is sequentially formed on a titanium stent, and finally a drug is loaded into the porous hydrogel coating, so that the implant has multiple properties such as antibacterial and osteosynthesis-promoting properties.
[0006] The present invention is achieved through the following technical scheme: a method for preparing an orthopedic implant with both antibacterial and osteogenic properties, wherein an acid-treated titanium stent is placed in a NaOH solution with a concentration of 200 mg / mL, and a sodium titanate coating is formed on the surface of the titanium stent after alkaline heat treatment;
[0007] After annealing, the coating was immersed in a mixed solution of 62.1 mg / mL EDTA-CaNa2 and 15.4 mg / mL NaH2PO4•2H2O, and a hydroxyapatite coating was formed on the surface of the sodium titanate coating after heating reaction;
[0008] Continue to immerse in a mixed solution of 20 mg / mL gluconolactone and 10 mg / mL sodium alginate, control the pH of the mixed solution to be 5, and form a porous hydrogel coating on the surface of the hydroxyapatite coating after the reaction;
[0009] After soaking the loaded medicine, the orthopedic implant is obtained.
[0010] The acid treatment is to immerse the titanium stent in a 20 mg / mL hydrofluoric acid solution for 10 minutes.
[0011] The alkaline heat treatment is carried out at 60° C. for 1 h.
[0012] The annealing was carried out in a muffle furnace at 600° C. for 1 h.
[0013] When the hydroxyapatite coating is formed by heating reaction, the temperature is heated to 180°C and the reaction time is 14 h.
[0014] When the porous hydrogel coating was formed by reaction, the reaction time was 1 h.
[0015] The drug includes one or more of vancomycin, teriparatide, denosumab, tranexamic acid and deoxyribonuclease I.
[0016] An orthopedic implant with antibacterial and osteogenesis properties is obtained by adopting the preparation method.
[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0018] (1) The coating of the present invention is a composite coating of hydroxyapatite and porous hydrogel. Drugs (such as antibiotics such as vancomycin and / or bone-promoting drugs such as teriparatide) are adsorbed in the porous hydrogel and sustainedly released locally to exert the functions of sterilization and / or bone promotion. At the same time, the degradation of the sodium alginate porous hydrogel coating will slowly release part of the Ca 2+ Promote bone growth into the implant, achieve biological fixation of the implant as soon as possible, prolong the survival time of the implant, and reduce the risk of postoperative revision.
[0019] (2) The present invention converts the titanium dioxide coating on the surface of the titanium stent into a sodium titanate coating through alkaline heat treatment. Sodium titanate has a loose and porous structure, good biological activity and a large specific surface area. During the hydrothermal process, sodium titanate can generate a large number of Ti-OH groups after hydration. Firstly, it can provide deposition sites for hydroxyapatite and bond with the coating in a chemical bond manner, thereby improving the bonding force between the hydroxyapatite coating and the titanium alloy surface and preventing it from falling off easily. Secondly, the generated sodium titanate coating has good biocompatibility and biological activity, and can improve the bone integration and osteogenic activity of the titanium alloy. Among them, since the sodium titanate coating itself has a loose and porous structure, it is conducive to bone ingrowth and physically locks with the coating, thereby improving bone integration. At the same time, due to the generated Ti-OH groups, it also provides favorable sites for osteoinduction, thereby improving osteogenic activity.
[0020] (3) In the preparation of the porous hydrogel coating, gluconolactone and sodium alginate are used in combination. The appropriate concentration of sodium gluconate can produce a slightly acidic environment, control the pH of the reaction system to 5, and slowly degrade the hydroxyapatite coating and release Ca 2+ , released Ca 2+ In situ cross-linking with sodium alginate on the surface of the stent forms a uniform porous gel. Therefore, for the method of the present invention, not only can a uniform porous hydrogel coating be obtained, but also the thickness of the porous hydrogel coating can be further controlled by controlling the reaction time, which is convenient for standardized production and control. Furthermore, the present invention can also make the porous hydrogel slowly degrade in the body fluid after the prosthesis is implanted in the body, and release Ca2+, which participates in the cross-linking of the hydrogel. 2+ , promote the bone ingrowth of the implant and achieve bone integration as soon as possible. The existing technology (such as CN112663057A) also has a hydroxyapatite coating and can also release Ca 2+ However, this process is extremely slow in the neutral pH environment in vivo. Therefore, for the present invention, Ca is synthesized in the slightly acidic environment provided by gluconolactone. 2+ The slow release of Ca can be formed by in situ cross-linking to form a controllable porous hydrogel. After implantation in the body, the sodium alginate hydrogel coating slowly degrades and the Ca released 2+ It can also promote bone cell growth and promote biological fixation of implants, which is expected to increase the service life of orthopedic implants.
[0021] (4) The present invention can also use other hydrogels cross-linked with calcium ions, such as gellan gum, which can also be in situ cross-linked on the surface of the hydroxyapatite coating to form a hydrogel coating, which has a wide range of applications.
[0022] (5) The present invention forms a composite coating of hydroxyapatite and porous hydrogel on a titanium stent and then loads the drug. In actual operation, the required drugs can be loaded in a personalized manner according to the clinical needs of the patients, such as coagulants such as tranexamic acid, drugs that inhibit osteoclasts such as bisphosphonates and denosumab, drugs that promote osteogenesis such as teriparatide, and drugs that inhibit bacterial biofilm formation such as deoxyribonuclease I. The implant and the drug can be stored and transported separately, which simplifies the production, storage and transportation process of the implant, brings great convenience to clinical application, and has great potential for clinical transformation.
[0023] (6) In the present invention, the in situ cross-linked porous hydrogel coating has excellent biosafety. Its gel properties make it widely used as a drug carrier and a scaffold material for tissue engineering in the medical field. Its polysaccharide properties and three-dimensional porous structure can well simulate the cell matrix, thereby providing a cell matrix-like environment for the growth of osteoblasts. The cell matrix-like porous gel environment can provide space for the growth of osteoblasts and is more conducive to the adhesion, growth and proliferation of osteoblasts. At the same time, as the Ca of the cross-linked sodium alginate hydrogel coating increases, 2+ The hydrogel coating is gradually released and absorbed by the cells, and the hydrogel coating will spontaneously match the tissue growth rate and degrade. Osteoblasts gradually grow into the porous structure of the hydroxyapatite coating on the implant surface, achieving organic bone integration between the host and the implant. The bridging process of the hydrogel coating is easier to achieve than the direct adhesion and growth of osteoblasts on the metal surface or hydroxyapatite surface.
[0024] In summary, the present invention is a process of using a titanium stent as a matrix to sequentially generate a sodium titanate coating, a hydroxyapatite coating and a porous hydrogel coating in situ to form a novel orthopedic implant. The combination of the sodium titanate coating, the hydroxyapatite coating and the porous hydrogel coating can improve the advantages of orthopedic implants in terms of antibacterial and osteogenic properties, especially promote the growth of bone cells and the biological fixation of implants, and improve the bone integration and osteogenic activity of titanium alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The X-ray diffraction (XRD) patterns of the stents of Example 1 and Comparative Example 1 are shown.
[0026] Figure 2 2 are scanning electron microscope images of the hydroxyapatite coatings of Example 1 and Comparative Example 1.
[0027] Figure 3 The figure is a comparison before and after cooling and drying of the plants in Example 1, Comparative Example 2 and Comparative Example 3.
[0028] Figure 4 These are scanning electron microscope images of the porous hydrogels after freeze-drying of the implants of Example 1 and Comparative Example 3.
[0029] Figure 5 It is the cumulative amount of calcium released by the implants of Example 1 and Comparative Example 2 in vitro at 37° C. for 72 h.
[0030] Figure 6 This is the Alizarin red staining control after the extracts of Example 1, Comparative Example 2 and Comparative Example 3 intervened in rat bone marrow mesenchymal stem cells.
[0031] Figure 7HE staining of the quadriceps femoris around the rat stent, where A is the cross section of the muscle fiber and B is the longitudinal section of the muscle fiber.
[0032] Figure 8 HE staining images of important organs of rats, where A is the heart, B is the liver, C is the spleen, D is the lung, and E is the kidney.
[0033] Fig. 9 This is a live imaging picture of the implant of Example 1 loaded with the fluorescent reagent indocyanine green and then implanted into a rat.
[0034] Fig.10 This is the antibacterial effect of the implant loaded with vancomycin in Example 1. DETAILED DESCRIPTION
[0035] The invention objectives, technical solutions and beneficial effects of the present invention are further described in detail below.
[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the claimed invention, and unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs.
[0037] The present invention aims to solve the problem that the existing orthopedic implant preparation methods are difficult to clinically transform and industrialize, and provides a preparation method for an orthopedic implant with a simple and easy-to-control preparation process and both antibacterial and osteogenic properties. The preparation method is prepared by sequentially forming a sodium titanate coating, a hydroxyapatite coating and a porous hydrogel coating on the surface of a titanium alloy stent, and finally loading a drug. The sodium titanate coating can provide a site for the deposition of the hydroxyapatite coating, improve the bonding ability of the hydroxyapatite coating with the surface of the titanium alloy stent, and also improve the bone integration and osteogenic activity of the titanium alloy stent; the composite coating of hydroxyapatite and porous hydrogel can not only load drugs to achieve functions such as sterilization and bone growth promotion, but also release part of Ca 2+ , promote the implant bone ingrowth, and realize the implant bone ingrowth biological fixation as soon as possible. At the same time, the preparation method of the present invention uses natural sodium alginate and gluconolactone with good biocompatibility, and its safety performance has been certified by FDA, and these substances are not chemically modified in the method of the present invention, so it has clinical transformation prospects.
[0038] For the present invention, the antibacterial and osteogenic properties are achieved through the following aspects:
[0039] 1) The hydrogel coating provided by the orthopedic implant of the present invention can be loaded with drugs, including but not limited to antibacterial drugs, drugs that inhibit bacterial biofilm formation, promote bone formation, inhibit osteoclasts and hemostasis drugs, so as to play corresponding roles. Therefore, the corresponding effects of the orthopedic implant of the present invention can be achieved by the loaded drugs, and the drugs can be loaded before the orthopedic implant is implanted into the host, so as to realize the separate production, sterilization and transportation of the implant and the drugs, which greatly facilitates the production and transportation of orthopedic implants and drugs.
[0040] 2) The hydroxyapatite coating provided by the orthopedic implant of the present invention has a certain osteogenic effect, but the porous sodium alginate hydrogel coating gradually degrades in the body and can appropriately accelerate the Ca 2+ Release, Ca 2+ The release of Ca has a promoting effect on the formation, adhesion and proliferation of osteoblasts. In actual application, after the hydrogel coating is gradually degraded and absorbed in the body, osteoblasts will gradually combine with the hydroxyapatite coating on the surface of the implant. 2+ The release of can promote osteoblasts to continue to adhere to the hydroxyapatite coating and continue to grow, and promote the bone integration of the host bone and the implant. Therefore, the combination of hydroxyapatite coating and hydrogel coating can achieve the biological fixation of the implant as soon as possible.
[0041] 3) The orthopedic implant of the present invention is prepared by a sodium titanate coating, which can improve the bonding strength between the hydroxyapatite coating and the titanium alloy surface and is not easy to fall off; at the same time, the porous structure and hydroxyl groups of the sodium titanate coating can also improve the bone integration and osteogenic activity of the titanium alloy, which is more conducive to promoting the bone integration of orthopedic implants.
[0042] The specific implementation modes of the present invention are described below in conjunction with the embodiments. Of course, the protection scope of the present invention is not limited to the following embodiments.
[0043] Example 1: Preparation of orthopedic implants
[0044] 1. Acid treatment:
[0045] The Ti6Al4V stent was immersed in a 20 mg / mL hydrofluoric acid solution for 10 min to remove the floating powder of the titanium alloy on the surface of the titanium stent to prevent the floating powder from falling off due to immersion in body fluids or friction after implantation in the human body, thereby causing inflammation.
[0046] (ii) Surface activation by alkali heat treatment:
[0047] The acid-treated Ti6Al4V scaffold was placed in a 200 mg / mL NaOH solution and subjected to alkaline heat treatment at 60°C for 1 h. The purpose was to convert the titanium dioxide coating on the surface of the Ti6Al4V scaffold into a sodium titanate coating. Sodium titanate has a loose and porous structure with good biological activity and a large specific surface area. The weakly alkaline sodium titanate coating can provide sites for the deposition of hydroxyapatite by providing hydroxyl groups.
[0048] (III) Annealing:
[0049] The Ti6Al4V bracket after the alkali heat treatment was placed in a muffle furnace and annealed at 600°C for 1 h to remove the bound water on its surface.
[0050] (IV) Hydrothermal deposition of hydroxyapatite coating:
[0051] The annealed Ti6Al4V scaffold was immersed in 80 mL of a mixed solution of 62.1 mg / mL EDTA-CaNa2 and 15.4 mg / mL NaH2PO4•2H2O, heated to 180°C at equal volumes, and reacted for 14 h.
[0052] (V) Preparation of sodium alginate hydrogel coating:
[0053] The hydroxyapatite-modified Ti6Al4V scaffold was immersed in a mixed solution of gluconolactone (20 mg / mL) and sodium alginate (10 mg / mL). The slightly acidic environment (pH 5) produced by gluconolactone with excellent biocompatibility slowly degraded the hydroxyapatite coating and released Ca 2+ , the released Ca 2+ Sodium alginate was cross-linked in situ on the surface of the scaffold to form a uniform porous gel. After soaking for about 1 hour, a porous hydrogel coating with a thickness of 1 mm was obtained. Deionized water was replaced several times to wash away the residual gluconolactone in the scaffold, and finally the scaffold was freeze-dried and stored at room temperature.
[0054] (VI) Porous hydrogel coating-hydroxyapatite-sodium titanate coating stent implantation:
[0055] During the operation, the porous hydrogel coating-hydroxyapatite-sodium titanate coating stent is immersed in an antibiotic and / or teriparatide solution for 1 to 2 minutes, wherein the concentration of the drug is determined according to the type of drug and clinical needs. After the drug is fully loaded, it is implanted in the body to achieve the sustained release of the above-mentioned drug, thereby exerting an antibacterial and / or osteogenic effect.
[0056] Comparative Example 1:
[0057] The difference between this comparative example and Example 1 is that: no alkaline heat treatment is used, and the surface activation of the acid-treated Ti6Al4V bracket is not performed. The acid-treated Ti6Al4V bracket is directly placed in a muffle furnace and annealed at 600°C for 1 h to remove the bound water on its surface, and then a hydroxyapatite coating is deposited on its surface. The specific control parameters for depositing the hydroxyapatite coating are the same as those in Example 1, thereby preparing a control bracket 1#.
[0058] Comparative Example 2:
[0059] The difference between this comparative example and Example 1 is that no gluconolactone was added during the preparation of the sodium alginate hydrogel coating.
[0060] Specifically, in this comparative example, a hydroxyapatite-modified Ti6Al4V scaffold was prepared in the same manner as in Example 1, and then immersed in a sodium alginate (10 mg / mL) solution having a neutral pH. After immersion for about 1 h, a control implant 2# was obtained.
[0061] Comparative Example 3:
[0062] The difference between this comparative example and Example 1 is that the control parameters for preparing the porous hydrogel coating are slightly different.
[0063] Specifically, in this comparative example, a hydroxyapatite-modified Ti6Al4V scaffold was prepared in the same manner as in Example 1, and then immersed in a mixed solution of gluconolactone (30 mg / mL) and sodium alginate (10 mg / mL), and the pH value of the mixed solution was controlled to be 4. After immersion for about 1 h, a porous hydrogel coating was obtained, and its thickness was about 3 mm (the thickness of the porous hydrogel coating is related to the pH. The lower the pH, the stronger the acidity, the faster the degradation of the hydroxyapatite coating, and the Ca 2+ The release is also faster, the faster the sodium alginate gel coating is formed). Thus, a control implant 3# was prepared.
[0064] The implants prepared in the above examples and comparative examples were subjected to the following experiments:
[0065] (1) Formation of hydroxyapatite coating
[0066] Taking the control stent 1# of comparative example 1 as a control, the hydroxyapatite-sodium titanate coated stent (i.e., the hydroxyapatite-modified Ti6Al4V stent) prepared in the above example 1 was subjected to electron microscope scanning and XRD diffraction to obtain the corresponding XRD patterns (see Figure 1 ) and SEM images of hydroxyapatite coatings (see Figure 2 ).
[0067] Depend on Figure 1It can be seen that the hydroxyapatite-sodium titanate coated stent of Example 1 can measure the specific XRD spectrum of hydroxyapatite, while the specific XRD spectrum of hydroxyapatite is not measured on the surface of the control stent 1# of Comparative Example 1; further, by Figure 2 It can be seen that the hydroxyapatite-sodium titanate coated stent of Example 1 has a hydroxyapatite coating with a cauliflower-shaped crystal structure, while no hydroxyapatite coating is formed on the surface of the control stent 1# of Comparative Example 1. This shows that the formation of the sodium titanate coating is a prerequisite for the formation of the hydroxyapatite coating. In Comparative Example 1, since the sodium titanate coating is not generated on the surface of the Ti6Al4V stent, it is impossible to provide a deposition site for hydroxyapatite, and therefore, no hydroxyapatite coating can be generated on the surface of the Ti6Al4V stent.
[0068] (2) Formation of porous hydrogel coating
[0069] The plants of Example 1, Comparative Example 2 and Comparative Example 3 were freeze-dried (-20°C, 24 h). The conditions before and after freeze-drying were recorded (see Figure 3 ).Depend on Figure 3 It can be seen that before freeze-drying, a uniform and transparent sodium alginate hydrogel coating was formed on the surface of Example 1, and after freeze-drying, it can be seen that the hydrogel coating is uniformly adhered to the surface of the stent; no sodium alginate hydrogel coating is formed on the surface of Comparative Example 2; a thicker hydrogel coating is formed on the surface of Comparative Example 3, with an irregular shape and uneven coating thickness, and after freeze-drying, it can be seen that the hydrogel coating completely covers the stent.
[0070] This proves that compared with Comparative Examples 2 and 3, Example 1 can provide a stable and controllable environment for the in-situ growth of sodium alginate on the surface of the hydroxyapatite coated stent by selecting an appropriate concentration of gluconolactone (20 mg / ml, pH=5). Comparative Examples 2 and 3 are not suitable for in-situ cross-linking of sodium alginate. In Comparative Example 2, since no gluconolactone is added, the pH of the solution is neutral. Under a neutral environment, the hydroxyapatite coating on the surface of the Ti6Al4V stent is difficult to degrade and release Ca 2+ , so sodium alginate cannot be cross-linked on the surface of the stent, and thus a porous hydrogel coating cannot be formed on the surface of the stent; in Comparative Example 3, since the concentration of gluconolactone is 30 mg / mL and the pH of the solution is 4, the acidity is stronger, which makes the hydroxyapatite coating degrade faster, Ca 2+ The generation of cross-linked hydrogels was also faster, and therefore, the cross-linked hydrogel coatings were thicker and less uniform.
[0071] Furthermore, the porous hydrogels on the surface of the freeze-dried stents (Example 1 and Comparative Example 3) were scanned by electron microscope (see Figure 4 ).Depend on Figure 4It can be seen that the hydrogel coating of Example 1 presents a loose porous structure, which provides a basis for loading drugs; the hydrogel coating formed in Comparative Example 3 is denser and less regular.
[0072] (3) Cumulative release of calcium in vitro
[0073] The implants of Example 1 and Comparative Example 2 were placed in 10 mL EP tubes, 2 mL of deionized water was added, and the tubes were placed on a shaker at 37°C. After 72 h, the liquid was collected, centrifuged at 5000 rpm, and the supernatant was collected. The calcium concentration was determined by inductively coupled plasma-mass spectrometry (ICP-MS) and the total amount of calcium released was calculated (see Figure 5 ).
[0074] Depend on Figure 5 It can be seen that Example 1 released about 40 μg of calcium, while Comparative Example 2 only released about 0.11 μg of calcium. This shows that the implant of Example 1 can release sufficient calcium as the sodium alginate hydrogel coating degrades, and these calcium elements provide a basis for the growth, proliferation and differentiation of osteoblasts after the implant is implanted in the body, while the calcium content released by Comparative Example 2 is too low to play the above role.
[0075] (4) Promote osteogenic differentiation of bone marrow mesenchymal stem cells
[0076] Bone marrow mesenchymal stem cells were isolated and extracted from rat bone marrow, and then the extracts of the plants in Example 1, Comparative Example 2, and Comparative Example 3 were extracted respectively to observe the effects of different extracts on promoting osteogenic differentiation of bone marrow mesenchymal stem cells (see Figure 6 ).
[0077] Depend on Figure 6 It can be seen that the extracts of Example 1, Comparative Example 2, and Comparative Example 3 can all promote the differentiation of bone marrow mesenchymal stem cells, but in the extract of Example 1, due to the degradation of the sodium alginate hydrogel coating, some Ca2+, which can promote the growth and differentiation of osteoblasts, is released. 2+ , Alizarin red staining showed that it can promote the osteogenic differentiation of bone marrow mesenchymal stem cells; Comparative Example 2 lacks gluconolactone, and the pH of the solution is neutral, so the hydroxyapatite-Ti6Al4V scaffold cannot release Ca 2+ Cross-linked sodium alginate, so the Ca content in the extract 2+ The content of Comparative Example 3 is negligible; due to the thicker hydrogel coating, the released Ca 2+ This shows that compared with Comparative Example 2, both Example 1 and Comparative Example 3 can promote the osteogenic differentiation of bone marrow mesenchymal stem cells, but the sodium alginate hydrogel coating of Comparative Example 3 has uneven thickness, irregular shape, and poor controllability of the reaction process.
[0078] (5) Biocompatibility and in vivo safety
[0079] The implant prepared in Example 1 was implanted subcutaneously on the outer thigh of rats. After 3 weeks, the muscle tissue near the stent and important organs (heart, liver, spleen, lung and kidney) were obtained, fixed with formalin and sliced, and HE staining was performed (see Figure 7 and Figure 8 ).
[0080] Depend on Figure 7 It can be seen that the muscle fibers of the rats implanted with Example 1 grew well, indicating that the implant of Example 1 would not cause abnormalities to the surrounding tissues after being implanted in the body, showing its good biocompatibility. Figure 8 It can be seen that after the implant of Example 1 was implanted in the body, no abnormalities such as degeneration and necrosis were observed in the tissues and cells in various organs, indicating that it has good in vivo safety.
[0081] (6) In vivo drug release
[0082] The fluorescent reagent indocyanine green was loaded into the porous hydrogel of the implant in Example 1 and implanted subcutaneously on the outer side of the right femur of rats. The fluorescent signals at different time stages after implantation were observed by a small animal in vivo imaging device (see Fig. 9 ).
[0083] Depend on Fig. 9 It can be seen that the in vivo imaging shows that the implant of Example 1 loaded with indocyanine green still has a strong local fluorescence signal 8 days after implantation in the body, indicating that the porous hydrogel coating of Example 1 has good ability to load and sustain drug release.
[0084] (7) Antibacterial properties
[0085] After the internal plant of Example 1 was loaded with vancomycin, the extract was mixed with a bacterial culture medium and used for bacterial culture to observe the antibacterial effect of the extract (see Fig.10 ).
[0086] Depend on Fig.10 It can be seen that the extract of Example 1 loaded with vancomycin can effectively inhibit the growth of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus, proving that the internal plant of Example 1 has excellent antibacterial properties after being loaded with vancomycin.
[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing an orthopedic implant having both antibacterial and osteogenic properties, characterized in that: The acid-treated titanium stent was placed in a 200 mg / mL NaOH solution, and a sodium titanate coating was formed on the surface of the titanium stent after alkaline heat treatment; After annealing, the coating was immersed in a mixed solution of 62.1 mg / mL EDTA-CaNa2 and 15.4 mg / mL NaH2PO4•2H2O, and a hydroxyapatite coating was formed on the surface of the sodium titanate coating after heating reaction; Continue to immerse in a mixed solution of 20 mg / mL gluconolactone and 10 mg / mL sodium alginate, control the pH of the mixed solution to be 5, and form a porous hydrogel coating on the surface of the hydroxyapatite coating after the reaction; After soaking the loaded medicine, the orthopedic implant is obtained.
2. The preparation method according to claim 1, characterized in that: The acid treatment is performed by immersing the titanium stent in a 20 mg / mL hydrofluoric acid solution and ultrasonically treating the titanium stent for 10 min.
3. The preparation method according to claim 1, characterized in that: The alkaline heat treatment is carried out at 60° C. for 1 h.
4. The preparation method according to claim 1, characterized in that: The annealing was carried out in a muffle furnace at 600° C. for 1 h.
5. The preparation method according to claim 1, characterized in that: When the hydroxyapatite coating is formed by heating reaction, the temperature is heated to 180°C and the reaction time is 14 h.
6. The preparation method according to claim 1, characterized in that: When the porous hydrogel coating was formed by reaction, the reaction time was 1 h.
7. The preparation method according to claim 1, characterized in that: The drug includes one or more of vancomycin, teriparatide, denosumab, tranexamic acid and deoxyribonuclease I.
8. An orthopedic implant having both antibacterial and osteogenesis properties, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of hydroxyapatite / drug-loaded hydrogel composite coating on surface of micro-arc titanium oxide
CN112663057A
Preparation method of hydrogel patch substrate with gradient drug concentration
CN103126975A
Surface porous bioactive implant and preparation method thereof
CN104689370A